2009
DOI: 10.2527/jas.2008-1493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential oils, tylosin, and monensin on finishing steer performance, carcass characteristics, liver abscesses, ruminal fermentation, and digestibility1

Abstract: A feedlot (Exp. 1) experiment was conducted to evaluate the effects of an essential oil mixture (EOM), experimental essential oil mixture (EXP), tylosin, and monensin (MON) on performance, carcass characteristics, and liver abscesses. A metabolism experiment (Exp. 2) was conducted to evaluate the effects of EOM, EXP, and MON on ruminal fermentation and digestibility in finishing steers. In Exp. 1, 468 yearling steers (398 ± 34 kg initial BW) were used in 50 pens (10 pens/treatment) and received their respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
92
5
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 28 publications
21
92
5
17
Order By: Relevance
“…The results for ADG and BW in this trial disagree with a large number of studies with essential oils, since Beauchemin et al (2006) and Meyer et al (2009) when supplementing beef cattle with essential oils, observed no difference in ADG compared with the control diets. Both authors emphasize that the lack of effect on performance is due to the similarity in dry matter intake of animals in different treatments.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…The results for ADG and BW in this trial disagree with a large number of studies with essential oils, since Beauchemin et al (2006) and Meyer et al (2009) when supplementing beef cattle with essential oils, observed no difference in ADG compared with the control diets. Both authors emphasize that the lack of effect on performance is due to the similarity in dry matter intake of animals in different treatments.…”
Section: Discussioncontrasting
confidence: 52%
“…With regard to the feed and conversion ratios in a similar experiment, Meyer et al (2009) observed no effect on feed efficiency in cattle supplemented with essential oils compared with the control diet. Moreover, Benchaar and McGinn (2008) when evaluating beef cattle fed 0.2 or 4 g/day of essential oils found a quadratic effect on feed efficiency, with it being better in the animals fed with 2 g of essential oil.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Benchaar et al (2006) fed crossbred steers and heifers (Angus vs. Hereford) with distinct levels (~250 or 500 mg/kg of DM) of a mix of essential oils (clove, vanillin, lemon and thymus), and no differences in FBW and ADG were observed. Likewise, no differences on FBW and ADG were observed when young steers received 80 mg/kg of DM of a mix of thymol, eugenol, vanillin, guaiacol and limonene (Meyer et al, 2009 (Benchaar & Greathead, 2011). Thus, essential oils can modulate the rumen microbiota, consequently affecting the production volatile organic compounds and protein degradation (Calsamiglia et al, 2007).…”
Section: Animal Performance and Feed Efficiencymentioning
confidence: 99%
“…Some essential oils have demonstrated strong antimicrobial, antifungal, anti-inflammatory and insecticidal activities [1,7,9,16,20]. Recently, there was extensive research on the biomedical applications in industrial animals served as antibiotic alternatives and natural insecticides [2,14,17,28].…”
mentioning
confidence: 99%